Hydrogen sulfide emissions from a swine building affected by dietary crude protein. (15th December 2017) - Liu, Shule; Ni, Ji-Qin; Radcliffe, John S.; Vonderohe, Caitlin
Abstract: Hydrogen sulfide (H2 S) is a toxic air pollutant at animal facilities; but the understanding of its generation and emission processes has been limited. This paper studied H2 S emissions during a complete cycle of wean–finish pigs from a research building, where 12 pig rooms were divided into three groups that were fed with standard feed (control), and 2.1–3.8% (T1 ) and 4.4–7.8% (T2 ) reduced dietary crude protein (CP) feed. The group cycle mean H2 S emission rates were 4.0 ± 2.9, 4.3 ± 3.2, and 5.4 ± 4.0 g d −1 AU −1 (Animal Unit = 500 kg live mass), respectively, for the control, T1, and T2 groups. Emissions of H2 S were promoted by 10.0 and 36.7%, respectively, for the T1 and T2 groups ( p  < 0.001), although large variabilities existed in the emissions from different rooms within the same groups. The enhanced H2 S emissions from the T1 and T2 groups were related to the reduced manure pH and were possibly affected through a number of pathways, which could involve volatile fatty acids and nitrogen concentrations, and microbial activities in manure. Highlights: Two groups of wean–finish pigs (T1 and T2 ) were fed with reduced crude protein diets. Emissions of H2 S increased by 10.0% (T1 ) and 36.7% (T2 ) compared with control group. Emissions of H2 S showed large temporal variations and were related to dietary phases. Manure pH was lower in the T1 and T2 groups than the control group. Necessity of long-term high-frequency monitoring of H2 S emissions was demonstrated.